Financial Knowledge, Spiritual Intelligence, and Hedonism Lifestyle of Department Store Employees in Managing Personal Finance - Sylvia, Sylvia; Adnan Aqsya, Mohammad; Mas’ud, Masdar (Entrepreneurship and Small Business Research, 2023)
The significance of financial management lies in its role as a crucial driver for realizing financial needs and achieving satisfaction in individual life, as it directly influences the likelihood of attaining financial freedom and preventing impulsive spending behaviors. This study aims to examine financial knowledge, spiritual intelligence, and hedonic lifestyle on financial management. The personal financial management behavior of employees of a well-known department store is addressed in this study by analyzing their financial knowledge, spiritual intelligence, and hedonistic lifestyle. Data was collected by surveying 84 employees of PT Ramayana Lestari Sentosa Makassar. The results of this study indicate that spiritual intelligence and financial knowledge have a positive and significant influence on employees' personal financial management while hedonism lifestyle has a negative and significant influence on employees' personal financial management. This shows that cognitive and spiritual intelligence factors can influence the way employees manage their personal finances. Meanwhile, a hedonistic lifestyle that leads actors to be consumptive has proven to make it difficult for employees to manage their personal finances.